Choice of Microbial System for In-Situ Resource Utilization on Mars - Averesch, Nils Jonathan Helmuth (Frontiers in Astronomy and Space Sciences, 2021)
Various microbial systems have been explored for their applicability to in-situ resource utilisation (ISRU) on Mars and suitability to leverage Martian resources and convert them into useful chemical products. Considering only fully bio-based solutions, two approaches can be distinguished, which comes down to the form of carbon that is being utilized: (a) the deployment of specialised species that can directly convert inorganic carbon (atmospheric CO2) into a target compound or (b) a two-step process that relies on independent fixation of carbon and the subsequent conversion of biomass and/or complex substrates into a target compound. Due to the great variety of microbial metabolism, especially in conjunction with chemical support-processes, a definite classification is often difficult. This can be expanded to the forms of nitrogen and energy that are available as input for a biomanufacturing platform. To provide a perspective on microbial cell factories that may be suitable for Space Systems Bioengineering, a high-level comparison of different approaches is conducted, specifically regarding advantages that may help to extend an early human foothold on the red planet.